2019
DOI: 10.1111/1742-6723.13275
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐blocker use is an independent risk factor for thunderstorm asthma

Abstract: Objective: To identify risk factors for thunderstorm asthma (TA) in subjects ≥15 years of age from information available in routine clinical records. Methods: Retrospective and hospital-based case-control study of various clinical factors in all TA cases (n = 53) who presented to a single-site ED in November 2016 (TA16) and in a control group of patients (n = 156) who presented to the same ED with asthma during the pollen season over eight non-TA years. Bivariate analysis and multivariable logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thunderstorms are an important risk factor for asthma hospital admissions. One study reported that, during a 12-h thunderstorm, asthma-related hospital admissions increased by almost 1000%, an unprecedented number that the health infrastructure was unprepared to handle [ 78 ]. During a thunderstorm, dry updrafts transport whole pollen grains to the cloud base's high humidity, which can lead to rupture, and cold downdrafts transport pollen fragments to the ground level, where outflows distribute them.…”
Section: Discussionmentioning
confidence: 99%
“…Thunderstorms are an important risk factor for asthma hospital admissions. One study reported that, during a 12-h thunderstorm, asthma-related hospital admissions increased by almost 1000%, an unprecedented number that the health infrastructure was unprepared to handle [ 78 ]. During a thunderstorm, dry updrafts transport whole pollen grains to the cloud base's high humidity, which can lead to rupture, and cold downdrafts transport pollen fragments to the ground level, where outflows distribute them.…”
Section: Discussionmentioning
confidence: 99%
“…43 In a slightly different clinical context, Sultana et al suggested that the use of beta-blockers was a risk factor for exacerbation related to thunderstorm asthma, but grouped non-selective and cardio-selective beta 1 -blockers together. 44 Among users of cardio-selective beta 1blockers there was no statistically significant increase in risk.…”
Section: Published Reportsmentioning
confidence: 95%
“…Those individuals who have experienced a particular outcome are the “cases” and those individuals who have not experienced that outcome are the controls 12,15 . For example, a recent case‐control study 16 “looked backward” at cases who had presented with thunderstorm asthma at an Australian hospital emergency department during the Melbourne pollen season of 2016. Cases were then compared with controls who had presented to the emergency department with asthma during the same period of time in earlier years.…”
Section: Introductionmentioning
confidence: 99%